Determinants of tourism in Asia Pacific - Chew, Zi Bin; Ding, Yi Yun; Pua, Wei Enn; Tan, Xing Yan; Wong, Huey (2019)
This paper investigates on how the macroeconomic factors (exchange rate, GDP, inflation and political stability) influence the tourism revenue (tourist arrivals and tourism receipts) in the top ten most visited Asia Pacific countries by employing several panel data approaches such as unit root test, co-integration test, long run estimates test and Dumitrescu-Hurlin Granger causality test with yearly time-series data from 2002 to 2016. We find that the exchange rate, GDP, inflation and political stability has long run relationship with tourist revenue but GDP has no causality (short run) relationship with tourist revenue in the ten countries that we conducted for the study. Also, policymaker can improve tourism growth and resolve the income inequality between developed and developing tourism-service dependent areas based on those macroeconomic factors.